2006
DOI: 10.1002/jsfa.2595
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the time and mode of application of gibberellic acid on the growth and yield of potato plants derived from true potato seed

Abstract: The effect of the time and mode of treatment (single or repeated applications) of gibberellic acid (GA 3 ) on the growth and tuberisation of plants grown from true seed (TPS) of potato Chacasina F 1 was studied. Plant height, fresh and dry weight of stems and leaf dry weight increased in response to single or repeated GA 3 applications. Leaf colour was not affected by single applications of GA 3 , whereas repeated applications caused a reduction in colour intensity. The numbers of secondary shoots and leaves p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…This role of gibberellin appears to be expressed through its inhibitory effect on tuberisation, since repeated applications of GA 3 starting 40 DAT significantly increased sprouting (Table 1) while at the same time reducing tuber yield. 15,16 However, exogenously supplied GA 3 may be metabolised at a different rate than gibberellins within the tubers, so the observed effects might differ from those produced by a rise in endogenous gibberellin levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This role of gibberellin appears to be expressed through its inhibitory effect on tuberisation, since repeated applications of GA 3 starting 40 DAT significantly increased sprouting (Table 1) while at the same time reducing tuber yield. 15,16 However, exogenously supplied GA 3 may be metabolised at a different rate than gibberellins within the tubers, so the observed effects might differ from those produced by a rise in endogenous gibberellin levels.…”
Section: Resultsmentioning
confidence: 99%
“…The application of GA 3 to plants from TPS has been shown to increase leaf area mainly as a result of increased leaf size, 12 whereas GA 3 increases leaf number in plants from seed tubers. 15 Moreover, repeated applications of GA 3 to plants from TPS initiated early in the growth cycle cause an increase in tuber number per plant, 16 whereas in plants from seed tubers the tuber number per plant is decreased by repeated GA 3 applications. 15 Apart from these examples, however, GA 3 appears to affect the sprouting of tubers from TPS in a similar way to those grown from seed tubers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports have revealed that the application of GA3 increased bulb weight in onion under deficit irrigation [63]. On the contrary, a few results have shown that the application of GAs caused a decline in tuber production in potato [64]; fruit production in sweet pepper [65], grape [66], and pear [67]; and root weight in carrot [59]. In potatoes, it was testified that GA3 treatment improved the number of tubers per plant [68].…”
Section: Gibberellic Acidmentioning
confidence: 99%
“…In addition, it has been stated that a high concentration of GA 3 and high frequency of application GA 3 inhibit lettuce growth [60] and decrease fruit weight in plum [81]. The application of GA 3 decreased root, tuber, fruit weight, and yield in other crops as well [59,64,67]. Previous reports have revealed that the application of GA 3 had a positive and negative effect on the organ nutritive eminence of potatoes, sweet peppers, and sweet cherries [65,82,83].…”
Section: Gibberellic Acidmentioning
confidence: 99%